Improvement of Administration System Management in the Metal and Plastic Industry that Implements the Job Order System - Rizka Nanda Saputri; Muhammad Hasyim Ashari (Santoso Academy Network, 2023)
The purpose of this community service activity is to improve the management of the administrative system in two divisions at PT Prima Sakti Asia, which was then adopted for other divisions within the company. The administrative system has an important role in providing data and information needed by the company, so improvements and development of a more effective and efficient administration system must be carried out to achieve company goals. This activity was carried out in two stages, namely work assistance and preparation of an administrative system. In carrying out this activity while assisting in preparing the administrative system, the personnel assigned to the Workshop Division and Maintenance Division found it helpful to improve the existing administrative governance. So it is easier to update regularly and continuously. The administrative system compiled by PT Prima Sakti Asia will be redeveloped for the other eight divisions. In addition, this activity increases the understanding of personnel in the Workshop Division and Maintenance Division in the administration field according to company needs. Of course, this will make it easier for personnel in each division to work better again in accordance with their duties and responsibilities